Off to a Bad Start: Youth Nonemployment and Labor Market Outcomes Later in Life - Mattia Filomena; Isabella Giorgetti; Matteo Picchio (Institute of Labor Economics (IZA), 2022)
We estimate the effect of nonemployment experienced by Italian youth after leaving secondary school on subsequent labor market outcomes. We focus on the impact on earnings and labor market participation both in the short- and in the long-term, up to 25 years since school completion. By estimating a factor analytic model which controls for time-varying unobserved heterogeneity, we find that the negative effect of nonemployment on earnings is especially persistent, being sizeable and statistically significant up to 25 years after school completion, for both men and women. Penalties in terms of participation last instead shorter; they disappear by the 10th year after school completion. Hence, early nonemployment operates by persistently locking the youth who get off to a bad start into low-wage jobs.
Keywords: J01; J08; J31; J64; 330; youth nonemployment; scarring effects; earnings; labor market participation; factor analytic model